Degradable anti-adhesion material and preparation method thereof

By crystallizing and crosslinking in a mixture of degradable polyester and hyaluronic acid, an anti-adhesion material with excellent biocompatibility, good tissue adhesion and controllable degradation cycle was prepared, which solved the shortcomings of existing materials in these aspects and achieved effective adhesion prevention and wound healing.

CN119524215APending Publication Date: 2025-02-28SHANGHAI FAWEI MEDICAL MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311103040.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing degradable anti-adhesive materials have shortcomings in tissue adhesion, mechanical properties and degradation cycles, resulting in poor effectiveness in preventing adhesions.

Method used

By mixing the degradable polyester and hyaluronic acid substances and crystallizing and crosslinking during heating and cooling, an anti-adhesion material with excellent biocompatibility, good tissue adhesion and controllable degradation cycle was prepared.

Benefits of technology

The material can maintain its complete form during the trauma repair period and degrade in the body in time. The degradation products are harmless and can be discharged quickly, effectively preventing adhesions and promoting healing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524215A_ABST
    Figure CN119524215A_ABST
Patent Text Reader

Abstract

The invention relates to a degradable anti-adhesion material and a preparation method thereof. The preparation method of the degradable anti-adhesion material comprises the following steps: providing degradable polyester and hyaluronic acid substances, wherein the tail ends of one or two of the degradable polyester and the hyaluronic acid substances are modified with carbon-carbon double bonds; the preparation method comprises the following steps: mixing degradable polyester, a hyaluronic acid substance, a first initiator and a crystallization nucleating agent, heating and pre-forming, cooling and crystallizing, and crosslinking carbon-carbon double bonds to prepare the degradable anti-adhesion material. According to the preparation method of the degradable anti-adhesion material, the tissue adhesion and the mechanical property can be improved, and the degradation period is proper.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of medical materials, and in particular to an anti-adhesion material and a preparation method thereof. Background Art

[0002] Adhesions are abnormal structures formed by the connection of connective tissue fiber bands with adjacent tissues or organs. They are prone to occur after surgery and are also common in the process of wound healing. In addition to tissue adhesions, they can also cause serious complications due to the different locations of adhesions. For example, if adhesions occur in the abdominal cavity, they can cause intestinal obstruction; if they occur in the pelvic cavity, they may cause pelvic pain or infertility. In addition to surgical trauma causing tissue adhesions, inflammation caused by local ischemia, the presence of foreign bodies in the body, and bacterial infections caused by wound exposure can also become causes of tissue adhesions.

[0003] At present, there are two main measures to prevent adhesions at home and abroad: one is to use physiological or pharmacological treatment mechanisms, such as reducing inflammatory reactions by applying anti-inflammatory drugs, antibiotics, etc., or giving electrical stimulation to reduce the incidence of adhesions; the other is to place physical barrier medical devices at the site where adhesions may occur. In order to avoid secondary trauma, the latter mostly uses degradable anti-adhesion materials, which can play an anti-adhesion role in the process of tissue healing and be decomposed or absorbed by themselves after surgery.

[0004] However, traditional degradable anti-adhesion materials still have the following problems: the tissue adhesion of anti-adhesion materials is poor, and they are easy to move with the activities of the organism, and need to be sutured and fixed, causing additional wounds; the mechanical strength of anti-adhesion materials is poor, and they cannot effectively play a physical barrier role in the early stage of wound repair; the degradation cycle of anti-adhesion materials does not match the wound healing cycle, which is too fast or too slow, and it is difficult to play a role in preventing tissue adhesion. For example, a traditional technology discloses a degradable medical anti-adhesion film, which is obtained by copolymerization of lactide and caprolactone. The product has good softness and strength, but the surface of the material is easy to adhere to proteins and cells, and the degradation rate is slow, which is inconsistent with the wound healing cycle. Another traditional technology provides a medical anti-adhesion film of polyester-polyether copolymer, which can be processed by single-layer casting, but the mechanical strength is low and the anti-adhesion effectiveness of the product is insufficient. Summary of the invention

[0005] Based on this, some embodiments of the present invention provide a degradable anti-adhesion material with good tissue adhesion, excellent mechanical properties and a suitable degradation cycle, and a preparation method thereof.

[0006] A method for preparing a degradable anti-adhesion material comprises the following steps:

[0007] Providing a degradable polyester and a hyaluronic acid substance, wherein one or both of the degradable polyester and the hyaluronic acid substance have a carbon-carbon double bond modified at their ends;

[0008] The degradable polyester, the hyaluronic acid substance, the first initiator and the crystallization nucleating agent are mixed, first heated for preforming, then cooled for crystallization, and then the carbon-carbon double bonds are cross-linked to prepare a degradable anti-adhesion material;

[0009] Wherein, the crystal nucleating agent includes one or more of cyclodextrin, orotic acid, zinc citrate, zinc chloride, zinc stearate, zinc acetate, magnesium stearate, calcium stearate, zinc alanine, zinc phenylalanine and zinc proline, and the mass of the crystal nucleating agent accounts for 0.05% to 5% of the total mass of the degradable polyester and the hyaluronic acid substance.

[0010] In some embodiments, the crystal nucleating agent satisfies one or both of the following conditions:

[0011] (1) The crystal nucleating agent includes zinc chloride and zinc stearate;

[0012] (2) The mass percentage of the crystal nucleating agent to the total mass of the degradable polyester and the hyaluronic acid substance is 0.2% to 0.5%.

[0013] In some embodiments, the hyaluronic acid substance satisfies one or more of the following conditions:

[0014] (1) The number average molecular weight of the hyaluronic acid substance is 20,000 to 2,000,000;

[0015] (2) Taking the total mass of the hyaluronic acid substance and the degradable polyester as 100%, the mass percentage of the hyaluronic acid substance is 1% to 60%, and the mass percentage of the degradable polyester is 40% to 99%.

[0016] In some embodiments, the hyaluronic acid substance satisfies one or more of the following conditions:

[0017] (1) The number average molecular weight of the hyaluronic acid substance is 100,000 to 1,000,000;

[0018] (2) Taking the total mass of the hyaluronic acid substance and the degradable polyester as 100%, the mass percentage of the hyaluronic acid substance is 10% to 50%, and the mass percentage of the degradable polyester is 50% to 90%.

[0019] In some embodiments, the steps for preparing the hyaluronic acid substance with a terminal modified carbon-carbon double bond include:

[0020] The hyaluronic acid substance, water, an alkaline agent, a first catalyst and glycidyl methacrylate are mixed and reacted to prepare a hyaluronic acid substance with a carbon-carbon double bond modified at the end;

[0021] Optionally, the molar ratio of the hyaluronic acid substance to the glycidyl methacrylate is 1:(10-50).

[0022] In some embodiments, the steps for preparing the degradable polyester with a terminal modified carbon-carbon double bond include:

[0023] Using a hydroxyl-containing compound or polymer as a second initiator, and in the presence of a second catalyst, polymerizing one or more monomers selected from L-lactide, D,L-lactide, glycolide, ε-caprolactone, ε-alkyl-substituted caprolactone, δ-alkyl-substituted valerolactone, orthoester and butylene succinate to prepare a polymer;

[0024] The polymer is reacted with a multifunctional compound to prepare a degradable polyester with a terminal modified with a carbon-carbon double bond, wherein one functional group of the multifunctional compound is capable of reacting with a hydroxyl group and another functional group includes a carbon-carbon double bond;

[0025] Optionally, the multifunctional compound includes one or more of acryloyl chloride, methacryloyl chloride, isocyanoethyl methacrylate, glycidyl methacrylate and propylene oxide acrylate.

[0026] In some embodiments, the preparation method satisfies one or more of the following conditions:

[0027] (1) In the heating preforming step, the temperature is 160° C. to 220° C., the time is 5 min to 12 min, and the pressure is 80 KN to 120 KN;

[0028] (2) In the step of cooling and crystallizing, the cooling rate is 10°C / min to 50°C / min;

[0029] (3) In the cross-linking step, the wavelength of light is 300 nm to 400 nm, the light exposure time is 10 min to 30 min, and the temperature is 80° C. to 130° C.

[0030] A method for preparing a degradable anti-adhesion material comprises the following steps:

[0031] The degradable polyester modified with a carbon-carbon double bond at the end is mixed with a first initiator and a crystal nucleating agent, first heated for preforming, then cooled for crystallization, and then the carbon-carbon double bonds are cross-linked to prepare a cross-linked polyester;

[0032] The cross-linked polyester is immersed in a hyaluronic acid solution and then dried to prepare a degradable anti-adhesion material;

[0033] Wherein, the crystal nucleating agent includes one or more of cyclodextrin, orotic acid, zinc citrate, zinc chloride, zinc stearate, zinc acetate, magnesium stearate, calcium stearate, zinc alanine, zinc phenylalanine and zinc proline, and the mass of the crystal nucleating agent accounts for 0.05% to 5% of the total mass of the degradable polyester and the hyaluronic acid substance.

[0034] In some embodiments, the preparation method satisfies one or more of the following conditions:

[0035] (1) The mass percentage concentration of the hyaluronic acid solution is 0.5% to 5%;

[0036] (2) The soaking time is 30 minutes to 12 hours;

[0037] (3) The drying step is carried out under vacuum conditions at a drying temperature of 30°C to 45°C.

[0038] A degradable anti-adhesion material is prepared by the above preparation method.

[0039] In some of the embodiments, the degradable anti-adhesion material includes a chemical cross-linked network and a physical crystallized network, and the chemical cross-linked network includes one or both of a three-dimensional cross-linked network and a semi-interpenetrating network formed by hyaluronic acid and degradable polyester.

[0040] The raw materials for preparing the above-mentioned degradable anti-adhesion material include hyaluronic acid substances and degradable polyesters. Hyaluronic acid substances can promote skin cell proliferation and fibrinolysis, inhibit inflammatory reactions, promote wound healing, and can adhere to tissues without suturing and fixing. In addition, by modifying at least one of the ends of hyaluronic acid substances and degradable polyesters with carbon-carbon double bonds, chemical cross-linking can be performed to form a cross-linked network, and a certain amount of crystal nucleating agent is added to induce the material to accelerate crystallization and increase the crystallinity, and synergize with the cross-linked network to achieve the purpose of improving the mechanical properties of the material and adjusting the degradation cycle of the material. During the wound repair period, the complete form can be maintained, and then degraded in the body, and the degradation products are harmless and can be quickly discharged from the body. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 is a process flow chart of a method for preparing a first degradable anti-adhesion material in some embodiments;

[0042] Figure 2 It is a process flow chart of the preparation method of the second degradable anti-adhesion material in other embodiments. DETAILED DESCRIPTION

[0043] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below in conjunction with the specific embodiments. Preferred embodiments of the present invention are provided in the specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0044] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0045] Unless otherwise specified or there is a contradiction, the terms or phrases used in this invention have the following meanings:

[0046] In the present invention, "first" and "second" are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features.

[0047] In the description of the present invention, “plurality” means at least two, for example, two, three, etc., unless otherwise clearly and specifically defined.

[0048] In the present invention, "one or several" refers to any one, any two or any two or more of the listed items. Among them, "several" refers to any two or any two or more.

[0049] In the present invention, the percentage concentration involved, unless otherwise specified, refers to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of the component.

[0050] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0051] When a numerical range is disclosed in the present invention, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise indicated, all ranges disclosed in the present invention should be understood to include any and all subranges included therein.

[0052] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0053] The terms "including" and "having" and any variations thereof in the embodiments of the present invention are intended to cover non-exclusive inclusions. For example, a process, method, system, product, or device that includes a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units that are not listed, or may optionally include other steps or components that are inherent to these processes, methods, products, or devices.

[0054] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.

[0055] A safe and effective anti-adhesion material should have good biocompatibility, reliable safety in use and appropriate tissue adhesion. It can maintain its intact form during the wound repair period, and then degrade in the body. The degradation products are harmless and can be quickly discharged from the body. However, the current anti-adhesion materials have poor biocompatibility, are prone to inflammatory reactions, have poor tissue adhesion, require suture fixation, have insufficient mechanical strength, and have a degradation cycle that is too short or too long. Based on this, some embodiments of the present invention provide a degradable anti-adhesion material and a preparation method thereof. The degradable anti-adhesion material has excellent biocompatibility, can effectively inhibit inflammation, promote wound repair, and has good tissue adhesion, does not require suture fixation during implantation, causing secondary trauma, and has excellent mechanical strength and a controllable degradation cycle.

[0056] Specifically, the first aspect of the present invention provides a method for preparing a first degradable anti-adhesion material, see Figure 1 , comprising the following preparation steps S110 to S120:

[0057] Step S120: providing a degradable polyester and a hyaluronic acid-based substance, wherein the ends of one or both of the degradable polyester and the hyaluronic acid-based substance are modified with a carbon-carbon double bond.

[0058] In some embodiments, taking the total mass of hyaluronic acid and degradable polyester as 100%, the mass percentage of hyaluronic acid is 1% to 60%, and the mass percentage of degradable polyester is 40% to 99%. For example, the mass percentage of hyaluronic acid can be, but is not limited to, 1%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or a range consisting of any two of these values. Optionally, the mass percentage of hyaluronic acid is 10% to 50%, and the mass percentage of degradable polyester is 50% to 90%. Optionally, the mass percentage of hyaluronic acid is 30% to 50%, and the mass percentage of degradable polyester is 50% to 70%. By optimizing the mass percentage of hyaluronic acid and degradable polyester, the compatibility of hyaluronic acid and degradable polyester can be adjusted, the mechanical properties can be improved, and the degradation cycle can be adjusted.

[0059] In certain embodiments, the number average molecular weight of hyaluronic acid is 20,000~2 million. For example, the number average molecular weight of hyaluronic acid is 20,000, 100,000, 200,000, 300,000, 400,000, 500,000, 600,000, 700,000, 800,000, 900,000, 1 million, 1.2 million, 1.5 million, 1.8 million, 2 million or any two of these values. Alternatively, the number average molecular weight of hyaluronic acid is 100,000~1 million. The compatibility of hyaluronic acid and degradable polyester can be adjusted by optimizing the molecular weight of hyaluronic acid, optimizing the mechanical properties and degradation cycle of degradable anti-adhesion material.

[0060] It can be understood that the hyaluronic acid-based substance can be hyaluronic acid, sodium hyaluronate, etc.

[0061] In some embodiments, the degradable polyester includes a polymer formed by one or more monomers selected from the group consisting of L-lactide, D,L-lactide, glycolide, ε-caprolactone, ε-alkyl-substituted caprolactone, δ-alkyl-substituted valerolactone, orthoesters, and butylene succinate.

[0062] In some embodiments, the degradable polyester further comprises a functional polymer, and the functional polymer includes but is not limited to one or a combination of two of polyethylene glycol and polyamino acid.

[0063] In some embodiments, the terminal of the degradable polyester is modified with a carbon-carbon double bond, and the preparation steps of the degradable polyester include S210 to S220:

[0064] Step S210: Using a hydroxyl-containing compound or polymer as a second initiator, and in the presence of a second catalyst, polymerizing one or more monomers selected from the group consisting of L-lactide, D,L-lactide, glycolide, ε-caprolactone, ε-alkyl-substituted caprolactone, δ-alkyl-substituted valerolactone, orthoester and butylene succinate to obtain a polymer.

[0065] Step S220: reacting the polymer with a multifunctional compound to obtain a degradable polyester with a terminal modified with a carbon-carbon double bond.

[0066] Specifically, the second catalyst includes one or more of aluminum isopropoxide, diethyl zinc, stannous octoate, stannous isooctanoate and stannous oleate.

[0067] Specifically, the second initiator includes a monohydric alcohol or a polyhydric alcohol compound or a polymer. Specifically, the second initiator includes one or more of ethylene glycol, butanol, butanediol, glycerol, pentaerythritol, dodecanol and polyethylene glycol.

[0068] Specifically, the number average molecular weight of the polymer is 10,000 to 100,000. For example, the number average molecular weight of the polymer can be, but is not limited to, 10,000, 20,000, 50,000, 80,000, 10,000, 12,000, 15,000, 18,000, 20,000, 22,000, 25,000, 28,000, 30,000, 32,000, 35,000, 38,000, 40,000, 42,000, 45,000, 48,000, 50,000, 60,000, 70,000, 80,000, 90,000, 100,000, or a range consisting of any two of these values. Optionally, the number average molecular weight of the polymer is 20,000 to 50,000.

[0069] Specifically, the multifunctional compound contains at least two functional groups, one of which can react with a hydroxyl group, and the other functional group includes a carbon-carbon double bond. Specifically, the functional group that can react with a hydroxyl group includes one of acyl chloride, anhydride, isocyanate and propylene oxide. In some embodiments, the multifunctional compound includes one or more of acryloyl chloride, methacryloyl chloride, isocyanoethyl methacrylate, glycidyl methacrylate and propylene oxide.

[0070] It is understood that if the degradable polyester does not contain carbon-carbon double bonds, step S220 is omitted. The degradable polyester is a base material that provides mechanical properties, and regulates the degradation time of the degradable anti-adhesion material through its own degradation rate and cycle.

[0071] Preferably, the terminal of the degradable polyester is modified with a carbon-carbon double bond. In the degradable anti-adhesion material, the degradable polyester forms a cross-linked network by itself or with hyaluronic acid substances, which can provide mechanical structural support for the material, improve tensile properties, and thus extend the degradation cycle of the material.

[0072] In some embodiments, the end of the hyaluronic acid substance is modified with a carbon-carbon double bond, and the preparation step of the hyaluronic acid substance includes: mixing the hyaluronic acid substance, water, an alkaline reagent, a first catalyst and glycidyl methacrylate to prepare a hyaluronic acid substance with a carbon-carbon double bond modified at the end.

[0073] In some embodiments, the alkaline agent includes triethylamine and the first catalyst includes tetrabutylammonium bromide.

[0074] In some embodiments, the molar ratio of hyaluronic acid (HA) to glycidyl methacrylate (GMA) is 1:(10-50). For example, the molar ratio of HA to GMA can be, but is not limited to, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, or a range consisting of any two of these values.

[0075] In some embodiments, the reaction time is 24 hours to 48 hours. For example, the reaction time can be, but is not limited to, 24 hours, 28 hours, 30 hours, 32 hours, 35 hours, 38 hours, 40 hours, 42 hours, 45 hours, 48 ​​hours, or a range consisting of any two of these values.

[0076] In some embodiments, the hyaluronic acid is first dissolved in water, and then an alkaline agent, a first catalyst and glycidyl methacrylate are added and mixed for reaction.

[0077] In some of the embodiments, after the mixing reaction is completed, dialysis and drying steps are further included.

[0078] Specifically, the dialysis step includes: dialysis in 0.1 mol / L sodium chloride solution and deionized water in sequence for 6 days.

[0079] Specifically, the drying step may be, but is not limited to, freeze drying.

[0080] It is understandable that the above only provides a method for modifying hyaluronic acid substances with carbon-carbon double bonds, but is not limited thereto. Other methods that can modify one end of a hyaluronic acid substance with a carbon-carbon double bond are also possible.

[0081] As a physical barrier material, hyaluronic acid can promote mesothelial cell proliferation and fibrinolysis, inhibit inflammatory response, and promote wound healing. Hyaluronic acid with high molecular weight and concentration is more effective in inhibiting inflammation and adhesion formation.

[0082] Step S120: mixing the degradable polyester, hyaluronic acid, the first initiator and the crystallization nucleating agent, first heating for preforming, then cooling for crystallization, and then cross-linking the carbon-carbon double bonds to prepare a degradable anti-adhesion material.

[0083] In some embodiments, the first initiator includes one or more of a photoinitiator and a thermal initiator. Specifically, the first initiator includes one or more of acylphosphorus oxide, dibenzoyl peroxide, benzophenone, 2,4-dihydroxybenzophenone and 4,4'-bis(dimethylamino)benzophenone. Specifically, the mass of the first initiator accounts for 0.5% to 5% of the total mass of the degradable polyester and the hyaluronic acid. For example, the mass of the first initiator accounts for a percentage of the total mass of the degradable polyester and the hyaluronic acid, but is not limited to 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or a range consisting of any two of these values.

[0084] In certain embodiments, the crystal nucleating agent comprises one or more combinations of cyclodextrin, orotic acid, zinc citrate, zinc chloride, zinc stearate, zinc acetate, magnesium stearate, calcium stearate, zinc alanine, zinc phenylalanine and zinc proline. Alternatively, the crystal nucleating agent comprises zinc chloride and zinc stearate. It is understood that zinc citrate can be, but is not limited to, a nano zinc citrate complex.

[0085] Specifically, the mass of the crystalline nucleating agent accounts for 0.05% to 5% of the total mass of the degradable polyester and the hyaluronic acid. For example, the mass of the crystalline nucleating agent accounts for a percentage of the total mass of the degradable polyester and the hyaluronic acid, but is not limited to 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5% or any two of these values. Optionally, the mass of the crystalline nucleating agent accounts for 0.05% to 0.5% of the total mass of the degradable polyester and the hyaluronic acid. Optionally, the mass of the crystalline nucleating agent accounts for 0.2% to 0.5% of the total mass of the degradable polyester and the hyaluronic acid substance.

[0086] By adding a crystal nucleating agent, during the cooling process after polymer hot pressing, the crystallization nucleation of the polymer is accelerated, the crystallization rate and degree of crystallinity are increased, and the mechanical strength of the material after molding is increased. The mechanical properties can be further improved and the degradation cycle of the material can be adjusted by optimizing the type or amount of the crystal nucleating agent.

[0087] In some embodiments, in the step of heating the preforming, the temperature is 160°C to 220°C, and the time is 5 min to 12 min. For example, in the step of heating the preforming, the temperature may be, but not limited to, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, or a range consisting of any two of these values, and the time may be, but not limited to, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, or a range consisting of any two of these values.

[0088] Furthermore, in the step of heating the preforming, the pressure is 80 KN to 120 KN. For example, the pressure may be, but is not limited to, 80 KN, 90 KN, 100 KN, 110 KN, 120 KN or a range consisting of any two of these values.

[0089] In some embodiments, in the step of cooling and crystallizing, the cooling rate is 10°C / min to 50°C / min. For example, the cooling rate can be, but is not limited to, 10°C / min, 15°C / min, 20°C / min, 25°C / min, 30°C / min, 35°C / min, 40°C / min, 45°C / min, 50°C / min, or a range consisting of any two of these values. At the above cooling rate, the degradable polyester slowly crystallizes under the action of the crystallization nucleating agent, further improving the crystallinity.

[0090] In some embodiments, in the cross-linking step, the wavelength of light exposure is 300 nm to 400 nm, the light exposure time is 10 min to 30 min, and the temperature is 80° C. to 130° C.

[0091] Optionally, the wavelength of the illumination may be, but is not limited to, 300 nm, 320 nm, 340 nm, 360 nm, 380 nm, 400 nm, or a range consisting of any two of these values.

[0092] Optionally, the illumination time may be, but is not limited to, 10 min, 12 min, 15 min, 18 min, 20 min, 22 min, 25 min, 28 min, 30 min, or a range consisting of any two of these values. The illumination temperature may be, but is not limited to, 80° C., 90° C., 100° C., 110° C., 120° C., 130° C., or a range consisting of any two of these values.

[0093] The raw materials for preparing the above-mentioned degradable anti-adhesion material include hyaluronic acid substances and degradable polyesters, wherein the hyaluronic acid substances can promote skin cell proliferation and fibrinolysis, inhibit inflammatory reactions, promote wound healing, and can adhere to tissues without suturing and fixation. In addition, by modifying the end groups of at least one of the hyaluronic acid substances and the degradable polyester with carbon-carbon double bonds, chemical cross-linking can be performed, and a crystal nucleating agent is added at the same time to induce the material to accelerate crystallization and increase the crystallinity, and the cross-linking network formed by chemical cross-linking synergizes to achieve the purpose of improving the mechanical properties of the material and regulating the degradation cycle of the material. During the wound repair period, the intact form can be maintained, and then degraded in the body, and the degradation products are harmless and can be quickly discharged from the body.

[0094] In addition, the above-mentioned degradable anti-adhesion material has good biocompatibility and will not cause inflammatory response after being implanted in the wound site. Moreover, the degradable anti-adhesion material has good water absorption and can quickly absorb water in a short time.

[0095] The present invention also provides a method for preparing a second degradable anti-adhesion material. Figure 2 , comprising the following preparation steps S310-S320:

[0096] Step S310: mixing the degradable polyester modified with a carbon-carbon double bond at the end with a first initiator and a crystal nucleating agent, first heating for preforming, then cooling for crystallization, and then cross-linking the carbon-carbon double bonds to prepare a cross-linked polyester.

[0097] It can be understood that the preparation steps of the degradable polyester modified with a carbon-carbon double bond at the end, the first initiator, the crystallization nucleating agent, the heating preforming step, the cooling crystallization step, and the cross-linking step are the same as those described above and will not be repeated.

[0098] Step S320: Soak the cross-linked polyester in a hyaluronic acid solution, and then dry it to prepare a degradable anti-adhesion material.

[0099] Specifically, hyaluronic acid is dissolved in water to form a hyaluronic acid solution of a certain concentration. In some embodiments, the mass percentage concentration of the hyaluronic acid solution is 0.5% to 5%. For example, the mass percentage concentration of the hyaluronic acid solution can be, but is not limited to, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or a range consisting of any two of these values. Optionally, the mass percentage concentration of the hyaluronic acid solution is 3% to 5%.

[0100] In some embodiments, in step S320, the soaking time is 30 minutes to 12 hours. For example, the soaking time can be, but is not limited to, 30 minutes, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 8 hours, 10 hours, 12 hours, or a range consisting of any two of these values. Optionally, the soaking time is 1 hour to 5 hours.

[0101] In some embodiments, the drying step is performed under vacuum conditions at a drying temperature of 30° C. to 45° C. For example, the drying temperature may be, but is not limited to, 30° C., 32° C., 35° C., 38° C., 40° C., 42° C., 45° C., or a range consisting of any two of these values. It is understood that drying can be stopped when the drying reaches a constant weight.

[0102] Compared with the method of directly melt blending to obtain a semi-interpenetrating network or three-dimensional cross-linked network structure of degradable polyester and hyaluronic acid substances, hyaluronic acid substances diffuse into the network structure formed by degradable polyester through solution, which can also achieve a certain effect of increasing the hydrophilicity of the material, and the mechanical properties are basically the same as the in vitro degradation rate. Moreover, a large amount of surface attachment of hydrophilic hyaluronic acid substances will cause the degradable anti-adhesion material to absorb water quickly in a short time. In the application scenario, direct contact with traumatic tissue may also exert its own anti-inflammatory, repair-promoting, and tissue adhesion-enhancing effects to a greater extent.

[0103] The second aspect of the present invention further provides a degradable anti-adhesion material, which is prepared by the preparation method of the first or second degradable anti-adhesion material.

[0104] In some embodiments, the degradable anti-adhesion material includes a chemical cross-linked network and a crystalline network. The chemical cross-linked network includes one or more of a three-dimensional cross-linked network and a semi-interpenetrating network formed by hyaluronic acid and degradable polyester.

[0105] In some of the embodiments, the three-dimensional cross-linked network can swell in a good solvent but cannot be dissolved. Specifically, the degradable polyester and the hyaluronic acid-based substance are connected by chemical bonds to form a three-dimensional cross-linked network.

[0106] In some of the embodiments, the semi-interpenetrating network is formed by interpenetrating polymer chains of at least one of the hyaluronic acid-based substance and the degradable polyester into a three-dimensional cross-linked network.

[0107] Specifically, in some embodiments, the end of the degradable polyester is modified with a carbon-carbon double bond, and in the degradable anti-adhesion material, the degradable polyester forms a three-dimensional cross-linked network, and the hyaluronic acid substance is physically mixed into the three-dimensional cross-linked network to form a semi-interpenetrating network. In other embodiments, the ends of the degradable polyester and the hyaluronic acid substance are both modified with a carbon-carbon double bond, and the degradable polyester and the hyaluronic acid substance form a three-dimensional cross-linked network together. In other embodiments, the ends of the degradable polyester and the hyaluronic acid substance are both modified with a carbon-carbon double bond, and the degradable polyester and the hyaluronic acid substance form a three-dimensional cross-linked network together, and the degradable polyester and the hyaluronic acid substance that are not cross-linked are partially mixed to form a semi-interpenetrating network. In other embodiments, the end of the hyaluronic acid substance is modified with a carbon-carbon double bond, and the hyaluronic acid substance forms a three-dimensional cross-linked network, and the degradable polyester is physically mixed into the three-dimensional cross-linked network to form a semi-interpenetrating network.

[0108] In some embodiments, the degradable anti-adhesion material has a certain hydrophilicity, a contact angle of 0 to 75°, and a saturated water absorption rate of 50% to 1500%.

[0109] For example, the saturated water absorption rate of the degradable anti-adhesion material can be, but is not limited to, 50%, 100%, 200%, 300%, 400%, 500%, 600%, 800%, 1000%, 1200%, 1500% or a range consisting of any two of these values. Optionally, the saturated water absorption rate of the degradable anti-adhesion material is 100% to 1000%.

[0110] For example, the contact angle of the degradable anti-adhesion material can be, but is not limited to, 0, 10°, 20°, 30°, 32°, 35°, 38°, 40°, 42°, 45°, 48°, 50°, 52°, 55°, 60°, 70°, 75° or any two of these values. Optionally, the contact angle of the degradable anti-adhesion material is 20° to 55°.

[0111] In some embodiments, the tensile strength of the degradable anti-adhesion material is 5MPa to 12MPa, and the elongation at break is 50% to 500%. For example, the tensile strength of the degradable anti-adhesion material can be, but is not limited to, 5MPa, 6MPa, 7MPa, 8MPa, 9MPa, 10MPa, 11MPa, 12MPa, or a range consisting of any two of these values. Optionally, the tensile strength is 6MPa to 12MPa.

[0112] For example, the elongation at break of the degradable anti-adhesion material can be, but is not limited to, 50%, 80%, 100%, 120%, 150%, 180%, 200%, 220%, 250%, 280%, 300%, 320%, 350%, 400%, 500% or any two of these values. Optionally, the elongation at break of the degradable anti-adhesion material is 50% to 350%.

[0113] In some embodiments, the complete degradation period of the degradable anti-adhesion material in an in vitro simulated degradation experiment at 37° C. with a degradation medium of PBS solution is 1 week to 30 weeks. For example, the complete degradation period can be, but is not limited to, 1 week, 2 weeks, 3 weeks, 4 weeks, 5 weeks, 6 weeks, 7 weeks, 8 weeks, 9 weeks, 10 weeks, 15 weeks, 20 weeks, 25 weeks, 30 weeks, or a range consisting of any two of these values. Optionally, the complete degradation period is 1 week to 10 weeks.

[0114] In some embodiments, the gel content of the degradable anti-adhesion material is 1 to 100%. For example, the gel content of the degradable anti-adhesion material can be, but is not limited to, 1%, 10%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100% or any two of these values. Optionally, in some embodiments, the gel content of the degradable anti-adhesion material is 20% to 100%. Further, the gel content of the degradable anti-adhesion material is 40% to 90%. Further, the gel content of the degradable anti-adhesion material is 70% to 90%.

[0115] The above-mentioned degradable anti-adhesion material is prepared from hyaluronic acid substances and degradable polyester. Hyaluronic acid substances can promote skin cell proliferation and fibrinolysis, inhibit inflammatory response, promote wound healing, and can adhere to tissues without suturing and fixation. Degradable polyester is used as a base material to provide mechanical properties, and regulates the degradation time of the degradable anti-adhesion material through its own degradation rate and cycle. In addition, a chemical cross-linking network and a crystalline network are formed between hyaluronic acid substances and degradable polyester. The two work synergistically to achieve the purpose of improving the mechanical properties of the material and regulating the degradation cycle of the material. During the wound repair period, the material can maintain its complete form and then degrade in the body. The degradation products are harmless and can be quickly discharged from the body.

[0116] In order to make the purpose and advantages of the present invention clearer, the degradable anti-adhesion material of the present invention and its effect are further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and shall not be used to limit the present invention. The following embodiments do not include other components except inevitable impurities unless otherwise specified. The drugs and instruments used in the embodiments are conventionally selected in this area unless otherwise specified. The experimental methods for which specific conditions are not specified in the embodiments are implemented according to conventional conditions, such as the conditions described in the literature, books, or the methods recommended by the manufacturer.

[0117] Example 1

[0118] This embodiment provides a degradable anti-adhesion material, and the preparation steps are as follows:

[0119] (1) Preparation of degradable polyesters with terminal groups modified with carbon-carbon double bonds:

[0120] Add 30g polyethylene glycol (M n =4000), vacuum dried in an oil bath at 90°C for 2h. Under nitrogen protection, 45g of racemic lactide (D,L-LA) and 15g of glycolide (GA) were added to the system, stirred and mixed for 0.5h, and then the catalyst stannous octoate (100ppm Sn) was added, and the temperature gradually increased to 140°C to start the polymerization reaction. After the polymerization was completed, 0.027g of inhibitor 4-p-methoxyphenol was added under nitrogen protection, stirred and mixed for 0.5h, and then 1.68g of isocyanoethyl methacrylate was added and stirred for 0.5h. The reaction was stopped to obtain a degradable polyester PDLGA-PEG-PDLGA block copolymer with carbon-carbon double bonds at both ends.

[0121] (2) Preparation of sodium hyaluronate with end groups modified with carbon-carbon double bonds:

[0122] 0.5 g of sodium hyaluronate with a number average molecular weight of 500,000 was added to 250 mL of deionized water and stirred to dissolve. Then 0.15 mL of triethylamine, 0.32 g of tetrabutylammonium bromide and 5.1 mL of glycidyl methacrylate GMA (the molar ratio of GMA to HA monomer was 30) were added in sequence. After 24 hours of reaction, the product was dialyzed in 0.1 mol / L NaCl solution and deionized water for 6 days, and then freeze-dried to obtain double-bond modified sodium hyaluronate HAGMA.

[0123] (3) Preparation of degradable anti-adhesion materials:

[0124] The double-bond modified degradable polyester obtained by (1) and (2) and the double-bond modified sodium hyaluronate were weighed 6.4g and 1.6g respectively, and blended with 0.04g of benzophenone, and then weighed 0.032g of zinc stearate. The mixed material was placed in a mold with a length and width of 100mm×100mm and a thickness of 500μm, and a layer of polytetrafluoroethylene film was covered on the top and bottom to facilitate demolding after hot pressing. Hot pressing at 190℃ and 80KN for 5min. After the hot pressing is completed, it is cooled to room temperature at a rate of 30℃ / min, and the upper polytetrafluoroethylene film is removed. Afterwards, the material is placed on a heating table at 130℃ and cross-linked under a UV lamp with a wavelength of 365nm for 10min. The material after cross-linking is placed at room temperature and demolded to obtain the degradable anti-adhesion material of this embodiment.

[0125] Example 2

[0126] This embodiment provides a degradable anti-adhesion material, which is similar to the preparation steps of the degradable anti-adhesion material of Example 1, except that: in step (3), 0.032 g of zinc chloride is used to replace 0.032 g of zinc stearate in Example 1, and the other steps are the same as Example 1 to obtain the degradable anti-adhesion material of this embodiment.

[0127] Example 3

[0128] The present embodiment provides a degradable anti-adhesion material, which is similar to the preparation steps of the degradable anti-adhesion material of Example 1, except that: in step (3), 0.016 g of zinc stearate and 0.016 g of zinc chloride are used to replace 0.032 g of zinc stearate in Example 1, and the other steps are the same as those in Example 1 to obtain the degradable anti-adhesion material of the present embodiment.

[0129] Example 4

[0130] This embodiment provides a degradable anti-adhesion material, and the preparation steps are similar to those of the degradable anti-adhesion material of Example 3, except that step (2) is different. Step (2) of this embodiment is specifically as follows:

[0131] 0.5 g of sodium hyaluronate with a number average molecular weight of 500,000 was added to 250 mL of deionized water and stirred to dissolve. Then 0.15 mL of triethylamine, 0.32 g of tetrabutylammonium bromide and 1.7 mL of glycidyl methacrylate GMA (the molar ratio of GMA to HA monomer was 10) were added in sequence. After reacting for 24 hours, the product was dialyzed in 0.1 mol / L NaCl solution and deionized water for 6 days, and then freeze-dried to obtain double-bond modified HAGMA.

[0132] Example 5

[0133] This embodiment provides a degradable anti-adhesion material, and the preparation steps are similar to those of the degradable anti-adhesion material of Example 3, except that step (2) is different. Step (2) of this embodiment is specifically as follows:

[0134] 0.5 g of sodium hyaluronate with a number average molecular weight of 500,000 was added to 250 mL of deionized water and stirred to dissolve. Then, 0.15 mL of triethylamine, 0.32 g of tetrabutylammonium bromide and 8.5 mL of glycidyl methacrylate GMA (the molar ratio of GMA to HA monomer was 50) were added in sequence. After 24 hours of reaction, the product was dialyzed in 0.1 mol / L NaCl solution and deionized water for 6 days, and then freeze-dried to obtain double-bond modified HAGMA.

[0135] Example 6

[0136] The present embodiment provides a degradable anti-adhesion material, which is similar to the preparation steps of the degradable anti-adhesion material of Example 3, except that: in the present embodiment, after completing the synthesis of the degradable polyester and the double bond modification of the terminal group in step (1), 6.4 g is weighed and blended with 1.6 g of sodium hyaluronate and 0.04 g of benzophenone, 0.016 g of zinc stearate and 0.016 g of zinc chloride that are directly weighed and not double-bond modified, and then processed and formed according to the steps in (3) to obtain the degradable anti-adhesion material of the present embodiment.

[0137] Example 7

[0138] This embodiment provides a degradable anti-adhesion material, which has similar preparation steps to the degradable anti-adhesion material of Example 3, except that: this embodiment only adjusts the number average molecular weight of sodium hyaluronate in (2) from 500,000 to 100,000, and the other raw material components and process steps are the same as those of Example 3.

[0139] Example 8

[0140] This embodiment provides a degradable anti-adhesion material, which has similar preparation steps to the degradable anti-adhesion material of Example 3, except that: this embodiment only adjusts the number average molecular weight of sodium hyaluronate in (2) from 500,000 to 1,000,000, and the other raw material components and process steps are the same as those of Example 3.

[0141] Example 9

[0142] The present embodiment provides a degradable anti-adhesion material, which has similar preparation steps to the degradable anti-adhesion material of Example 3, except that: in the present embodiment, only the mass ratio of the double-bond modified degradable polyester and sodium hyaluronate used in (3) is adjusted from 6.4g:1.6g to 4g:4g, and the other raw material components and process steps are the same as those of Example 3 to obtain the degradable anti-adhesion material of the present embodiment.

[0143] Example 10

[0144] The present embodiment provides a degradable anti-adhesion material, which has similar preparation steps to the degradable anti-adhesion material of Example 3, except that: in the present embodiment, only the mass ratio of the double-bond modified degradable polyester and sodium hyaluronate used in (3) is adjusted from 6.4g:1.6g to 7.2g:0.8g, and the other raw material components and process steps are the same as those of Example 3 to obtain the degradable anti-adhesion material of the present embodiment.

[0145] Embodiment 11

[0146] The present embodiment provides a degradable anti-adhesion material, which has similar preparation steps to the degradable anti-adhesion material of the embodiment 3, except that: the present embodiment only makes an adjustment to (1). After the polymerization reaction of the degradable polyester is completed, it is directly processed and shaped and cross-linked by light according to the steps in (2) and (3) without double bond modification to obtain the degradable anti-adhesion material of the present embodiment.

[0147] Example 12

[0148] The present embodiment provides a degradable anti-adhesion material, and the preparation steps of the degradable anti-adhesion material are similar to those of the present embodiment 1, except that: in step (3), 0.032 g of cyclodextrin is used to replace 0.032 g of zinc stearate in the present embodiment 1, and the other steps are the same as those of the present embodiment 1 to obtain the degradable anti-adhesion material of the present embodiment.

[0149] Embodiment 13

[0150] The present embodiment provides a degradable anti-adhesion material, which is similar to the preparation steps of the degradable anti-adhesion material of Example 3, except that: in step (3), the added amount of zinc stearate and zinc chloride is doubled, and both are increased from 0.016g to 0.032g, respectively, and the other steps are the same as Example 3 to obtain the degradable anti-adhesion material of the present embodiment.

[0151] Embodiment 14

[0152] This embodiment provides a degradable anti-adhesion material, and the preparation steps are as follows:

[0153] (1) Preparation of degradable polyesters with terminal groups modified with carbon-carbon double bonds:

[0154] According to step (1) in Example 1, a degradable polyester PDLGA-PEG-PDLGA block copolymer modified with carbon-carbon double bonds at both ends was prepared.

[0155] (2) Preparation of cross-linked polyester:

[0156] Weigh 8g of biodegradable polyester modified with carbon-carbon double bonds at both ends and blend with 0.04g of benzophenone, 0.016g of zinc stearate and 0.016g of zinc chloride, then place the mixed material in a mold with a length and width of 100mm×100mm and a thickness of 500μm, and cover the upper and lower layers of polytetrafluoroethylene film to facilitate demolding after hot pressing. Hot press at 190℃ and 80KN for 5min. After the hot pressing is completed, cool to room temperature and remove the upper polytetrafluoroethylene film. After that, place the material on a heating table at 130℃ and crosslink under a UV lamp with a wavelength of 365nm for 10min. After the crosslinking is completed, the material is placed at room temperature and demolded to obtain a cross-linked polyester.

[0157] (3) Preparation of degradable anti-adhesion materials:

[0158] 0.06 g of sodium hyaluronate with a number average molecular weight of 100,000 was dissolved in 20 mL of deionized water, stirred and dissolved at room temperature to prepare a sodium hyaluronate solution with a mass percentage concentration of 3%. The cross-linked polyester obtained above was soaked in the sodium hyaluronate solution for 12 hours. The material was then taken out, placed in a vacuum oven at 37°C, and dried to constant weight to obtain the degradable anti-adhesion material of this embodiment.

[0159] Comparative Example 1

[0160] Comparative Example 1 provides a degradable anti-adhesion material, which differs from Example 1 in that no crystal nucleating agent is added in step (3).

[0161] Comparative Example 2

[0162] Comparative Example 2 provides a degradable anti-adhesion material, which has similar preparation steps to the degradable anti-adhesion material of Example 1, except that: in this example, after completing the polymerization reaction of the degradable polyester in step (1), 6.4 g is directly weighed without terminal double bond modification, and blended with 1.6 g of sodium hyaluronate without double bond modification and 0.04 g of benzophenone, and then processed and formed according to the steps in (3) to obtain the degradable anti-adhesion material of Comparative Example 2.

[0163] Comparative Example 3

[0164] Comparative Example 3 provides a degradable anti-adhesion material, which is similar to the preparation steps of the degradable anti-adhesion material of Example 1, except that: in this example, after completing the polymerization reaction of the degradable polyester in step (1), 6.4 g is directly weighed without terminal double bond modification, and blended with 1.6 g of sodium hyaluronate that is not double bond modified, 0.04 g of benzophenone, and 0.032 g of zinc stearate, and then processed and formed according to the steps in (3) to obtain the degradable anti-adhesion material of Comparative Example 3.

[0165] The following is the test part:

[0166] The degradable anti-adhesion materials obtained in the above examples and comparative examples were tested according to the following steps:

[0167] (1) Saturated water absorption rate: Cut the degradable anti-adhesion material into a shape of 20 mm × 20 mm × 0.5 mm, weigh the initial mass, record it as W0. Then place it in a PBS solution at 37°C, take it out after 24 hours, use filter paper to absorb the surface water, weigh the mass again, record it as W1. The saturated water absorption rate is calculated according to A = (W1-W0) / W0×100%;

[0168] (2) Contact angle: Cut the degradable anti-adhesion material into a shape of 40 mm × 40 mm and measure the contact angle of water using a contact angle meter;

[0169] (3) Gel content: Weigh a certain mass of the degradable anti-adhesion material, record the initial mass as W0, and immerse it in dichloromethane. After 24 hours, take out the degradable anti-adhesion material, dry it in a fume hood for 4 hours, weigh the material mass, record it as W1. The formula for calculating the gel content is G = W1 / W0 × 100%;

[0170] (4) Tensile strength and elongation at break: According to the provisions of GB13022-91, the prepared degradable anti-adhesion material was cut into a dumbbell shape, and the tensile strength and elongation at break were tested using a universal tensile testing machine;

[0171] (5) In vitro degradation cycle at 37°C: The degradable anti-adhesion material was cut into a shape of 30 mm × 10 mm × 0.5 mm, immersed in a 37°C PBS solution, and the time for the degradable anti-adhesion material to completely degrade and disappear was recorded.

[0172] Table 1 below is a table of performance parameter results obtained from testing the degradable anti-adhesion materials prepared in Examples 1 to 14 and Comparative Examples 1 to 3:

[0173] Table 1 Performance data of degradable anti-adhesion materials of various embodiments and comparative examples

[0174]

[0175]

[0176] As can be seen from Table 1 above, compared with Comparative Example 1, the results of Example 1 and Example 2 show that in the degradable anti-adhesion material, the addition of a crystalline nucleating agent may improve the mechanical strength of the material by increasing the crystallinity of the degradable polyester in the material component, thereby extending the degradation cycle of the material. The results of Example 3 show that by introducing a composite nucleating agent, the crystallinity of the degradable polyester in the material component may be further improved compared to a single nucleating agent, and the mechanical strength of the material is increased accordingly, and the degradation cycle is also extended to a certain extent.

[0177] Compared with Example 3, the performance test results of Examples 4 to 6 show that: the three-dimensional cross-linked network or semi-interpenetrating network constructed by degradable polyester and sodium hyaluronate, with the increase of the double bond modification content of sodium hyaluronate, the gel content and tensile strength of the obtained degradable anti-adhesion material gradually increase, the saturated water absorption rate gradually decreases, and the in vitro degradation period at 37°C can be regulated within 3 weeks to 6.5 weeks.

[0178] Compared with Example 3, the performance test results of Comparative Example 2 show that when the degradable polyester and hyaluronic acid are directly blended without any double bond modification to obtain a degradable anti-adhesion material, due to the good hydrophilicity of sodium hyaluronate, while increasing the water absorption rate of the material, it also accelerates the hydrolysis rate of the degradable polyester, shortening the in vitro degradation period of the material to 1 week.

[0179] Compared with Example 3, the performance test results of Examples 7 to 8 show that: within a certain range, when the molecular weight of sodium hyaluronate is increased, the tensile strength and 37°C in vitro degradation cycle of the obtained degradable anti-adhesion material are improved, and the elongation at break is reduced. This may be because, in the degradable anti-adhesion material, the molecular weight of sodium hyaluronate of the same mass ratio is increased, and the strength is increased, but the molecular weight of sodium hyaluronate continues to increase, and the compatibility with the degradable polyester becomes worse, and the possibility of reacting with the terminal double bond of the degradable polyester to form a cross-linked network is reduced, and it is easier to form a significant two-phase separation, causing mechanical defects in the material, which in turn causes a decrease in strength.

[0180] Compared with Example 3, the results of Examples 9 to 10 show that the increase in the mass proportion of sodium hyaluronate in the degradable anti-adhesion material will significantly improve the hydrophilicity of the material; but if the proportion is too high, the compatibility with the degradable polyester will deteriorate, which will reduce the elongation at break and accelerate the degradation rate of the material.

[0181] Compared with Example 3, the results of Example 11 indicate that in the degradable anti-adhesion material, if the degradable polyester does not form a cross-linked network by itself or with sodium hyaluronate, the hydrophilicity of the material will be improved and the saturated water absorption space will be increased, but the material will lose its mechanical structural support, the tensile properties will be reduced, and the material degradation cycle will be shortened accordingly.

[0182] The performance test results of Example 14, Example 3 and Example 6 show that: compared with direct melt blending, a semi-interpenetrating network or three-dimensional cross-linked network structure of degradable polyester and sodium hyaluronate is obtained, and sodium hyaluronate diffuses into the network structure through the solution, which can also achieve a certain effect of increasing the hydrophilicity of the material, and the mechanical properties are basically the same as the in vitro degradation rate. Moreover, a large amount of surface attachment of hydrophilic sodium hyaluronate will cause the anti-adhesion material to absorb water quickly in a short time; in the application scenario, direct contact with the traumatic tissue may also exert its own anti-inflammatory and repair-promoting effects and enhance tissue adhesion to a greater extent.

[0183] It can be seen from the above experimental results that the degradable anti-adhesion material prepared in the above embodiment has at least the following advantages:

[0184] (1) The introduction of hyaluronic acid components in the degradable anti-adhesion material can make the material have anti-inflammatory and repair-promoting effects while the material itself has degradability and physical barrier properties, and can adhere to tissues without suturing and fixation.

[0185] (2) The semi-interpenetrating network formed by hyaluronic acid and cross-linked degradable polyester in the degradable anti-adhesion material, or the three-dimensional cross-linked network formed by hyaluronic acid and degradable polyester, can effectively enhance the mechanical properties of the material, and can also regulate the degradation cycle of the material and prolong its action time by adjusting parameters such as cross-linking density.

[0186] (3) The addition of a crystal nucleating agent to the above-mentioned degradable anti-adhesion material can improve the crystallinity of the degradable polyester in the material component, synergistically with the chemical cross-linking effect, thereby improving the mechanical strength of the material and extending the degradation cycle of the material.

[0187] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0188] The above-described embodiments only express several implementation methods of the present invention, which is convenient for understanding the technical solutions of the present invention in detail, but cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided by the present invention are all within the protection scope of the claims attached to the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the contents of the attached claims, and the description and drawings can be used to interpret the contents of the claims.

Claims

1. A method for preparing a degradable anti-adhesion material, characterized in that: The steps include: Providing a degradable polyester and a hyaluronic acid substance, wherein one or both of the degradable polyester and the hyaluronic acid substance have a carbon-carbon double bond modified at their ends; The degradable polyester, the hyaluronic acid substance, the first initiator and the crystallization nucleating agent are mixed, first heated for preforming, then cooled for crystallization, and then the carbon-carbon double bonds are cross-linked to prepare a degradable anti-adhesion material; Wherein, the crystal nucleating agent includes one or more of cyclodextrin, orotic acid, zinc citrate, zinc chloride, zinc stearate, zinc acetate, magnesium stearate, calcium stearate, zinc alanine, zinc phenylalanine and zinc proline, and the mass of the crystal nucleating agent accounts for 0.05% to 5% of the total mass of the degradable polyester and the hyaluronic acid substance.

2. The method for preparing the degradable anti-adhesion material according to claim 1, characterized in that: The crystal nucleating agent satisfies one or two of the following conditions: (1) The crystal nucleating agent includes zinc chloride and zinc stearate; (2) The mass percentage of the crystal nucleating agent to the total mass of the degradable polyester and the hyaluronic acid substance is 0.2% to 0.5%.

3. The method for preparing the degradable anti-adhesion material according to any one of claims 1 to 2, characterized in that: The hyaluronic acid substance meets one or more of the following conditions: (1) The number average molecular weight of the hyaluronic acid substance is 20,000 to 2,000,000; (2) Taking the total mass of the hyaluronic acid substance and the degradable polyester as 100%, the mass percentage of the hyaluronic acid substance is 1% to 60%, and the mass percentage of the degradable polyester is 40% to 99%.

4. The method for preparing the degradable anti-adhesion material according to claim 3, characterized in that: The hyaluronic acid substance meets one or more of the following conditions: (1) The number average molecular weight of the hyaluronic acid substance is 100,000 to 1,000,000; (2) Taking the total mass of the hyaluronic acid substance and the degradable polyester as 100%, the mass percentage of the hyaluronic acid substance is 10% to 50%, and the mass percentage of the degradable polyester is 50% to 90%.

5. The method for preparing the degradable anti-adhesion material according to any one of claims 1 to 2 and 4, characterized in that: The preparation steps of the hyaluronic acid substance with a carbon-carbon double bond modified at the end include: The hyaluronic acid substance, water, an alkaline agent, a first catalyst and glycidyl methacrylate are mixed and reacted to prepare a hyaluronic acid substance with a carbon-carbon double bond modified at the end; Optionally, the molar ratio of the hyaluronic acid substance to the glycidyl methacrylate is 1:(10-50).

6. The method for preparing the degradable anti-adhesion material according to any one of claims 1 to 2, characterized in that: The preparation steps of the degradable polyester with a terminal modified carbon-carbon double bond include: Using a hydroxyl-containing compound or polymer as a second initiator, and in the presence of a second catalyst, polymerizing one or more monomers selected from L-lactide, D,L-lactide, glycolide, ε-caprolactone, ε-alkyl-substituted caprolactone, δ-alkyl-substituted valerolactone, orthoester and butylene succinate to prepare a polymer; The polymer is reacted with a multifunctional compound to prepare a degradable polyester with a terminal modified with a carbon-carbon double bond, wherein one functional group of the multifunctional compound is capable of reacting with a hydroxyl group and another functional group includes a carbon-carbon double bond; Optionally, the multifunctional compound includes one or more of acryloyl chloride, methacryloyl chloride, isocyanoethyl methacrylate, glycidyl methacrylate and propylene oxide acrylate.

7. The method for preparing the degradable anti-adhesion material according to any one of claims 1 to 2, characterized in that: The preparation method meets one or more of the following conditions: (1) In the heating preforming step, the temperature is 160° C. to 220° C., the time is 5 min to 12 min, and the pressure is 80 KN to 120 KN; (2) In the step of cooling and crystallizing, the cooling rate is 10°C / min to 50°C / min; (3) In the cross-linking step, the wavelength of light is 300 nm to 400 nm, the light exposure time is 10 min to 30 min, and the temperature is 80° C. to 130° C.

8. A method for preparing a degradable anti-adhesion material, characterized in that: The steps include: The degradable polyester modified with a carbon-carbon double bond at the end is mixed with a first initiator and a crystal nucleating agent, first heated for preforming, then cooled for crystallization, and then the carbon-carbon double bonds are cross-linked to prepare a cross-linked polyester; The cross-linked polyester is immersed in a hyaluronic acid solution and then dried to prepare a degradable anti-adhesion material; Wherein, the crystal nucleating agent includes one or more of cyclodextrin, orotic acid, zinc citrate, zinc chloride, zinc stearate, zinc acetate, magnesium stearate, calcium stearate, zinc alanine, zinc phenylalanine and zinc proline, and the mass of the crystal nucleating agent accounts for 0.05% to 5% of the total mass of the degradable polyester and the hyaluronic acid substance.

9. The method for preparing the degradable anti-adhesion material according to claim 8, characterized in that: The preparation method meets one or more of the following conditions: (1) The mass percentage concentration of the hyaluronic acid solution is 0.5% to 5%; (2) The soaking time is 30 minutes to 12 hours; (3) The drying step is carried out under vacuum conditions at a drying temperature of 30°C to 45°C.

10. A degradable anti-adhesion material, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 9.

11. The degradable anti-adhesion material according to claim 10, characterized in that: The degradable anti-adhesion material comprises a chemical cross-linking network and a crystalline network. The chemical cross-linking network comprises one or both of a three-dimensional cross-linking network and a semi-interpenetrating network formed by hyaluronic acid substances and degradable polyesters.